The only superpower reflections on strength, weakness, and anti-Americanism - Hollander, Paul (Lexington Books, 2009)
The essays in The Only Super Power deal with present day American Society_its problems, critiques, and perceptions at home and abroad_with special reference to mass culture, multiculturalism, and radical Islam. Other items examine the aftermath of and continued responses to the fall of Soviet communism and the remaining communist systems